DETERMINAN FINANCIAL DISTRESS PERUSAHAAN SUBSEKTOR RITEL DI BURSA EFEK INDONESIA: DETERMINANT OF FINANCIAL DISTRESS ON THE RETAIL SUBSECTOR PUBLIC COMPANIES IN INDONESIA STOCK EXCHANGE - Dony Firman Santosa; Lukytawati Anggraeni; Koes Pranowo (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The purpose of this study were (1) To analyze financial health conditions of retail companies listed in Indonesia Stock Exchange (IDX) from 2013 to 2017, (2) To analyze the relationship between financial health conditions with companies’ status based on an integral process of financial distress using Pearson correlation and (3) To analyze what factors (financial ratios and macroeconomics) which affected to financial distress using panel data regression. Fourteen retail companies were selected as samples based on purposive sampling. The results showed that retail companies in telecommunication devices, building materials, convenience store models and minimarkets had more potential to experience financial distress. The results of the Pearson correlation showed that there was a weak and negative correlation between DSCR as a proxy of financial distress with deterioration performance and cash flow problem. The financial ratio variables such as, the current ratio and return on equity, had a positive and significant effect on DSCR. Whereas, the debt to equity ratio had a negative and significant effect on DSCR. Meanwhile, significant macroeconomic variables were gross domestic product and interest rate. Gross domestic product had a positive effect on DSCR, while interest rates had a negative effect on DSCR. Keywords: financial distress (debt service coverage ratio), financial ratios, macroeconomic, panel data regression, retail companies Abstrak: Tujuan dari penelitian ini adalah (1) Menganalisis kondisi kesehatan keuangan perusahaan subsektor ritel yang terdaftar di Bursa Efek Indonesia dari tahun 2013 sampai 2017, (2) Menganalisis hubungan kondisi kesehatan keuangan dengan status perusahaan berdasarkan proses integral financial distress menggunakan analisis korelasi pearson dan (3) Menganalisis faktor-faktor keuangan dan makroekonomi yang berpengaruh terhadap financial distress menggunakan analisis regresi data panel. Sebanyak 14 perusahaan ritel dipilih sebagai sampel menggunakan purposive sampling. Hasil penelitian menunjukan bahwa perusahaan ritel yang bergerak dalam bidang usaha perangkat telekomunikasi, bahan bangunan, model conveience store dan minimarket lebih berpotensi mengalami financial distress. Hasil analisis korelasi pearson menunjukan terdapat korelasi negatif yang lemah antara DSCR sebagai proxy financial distress dengan deterioration performance dan cash flow problem. Variabel rasio keuangan seperti current ratio dan return on equity berpengaruh positif dan signifikan terhadap DSCR, sedangkan debt to equity ratio memiliki pengaruh negatif dan signifkan terhadap DSCR. Sementara itu, variabel makroekonomi yang signifikan adalah gross domestic product dan interest rate. Gross domestic product berpengaruh positif terhadap DSCR sedangkan interest rate memiliki pengaruh negatif terhadap DSCR. Kata kunci: kesulitan keuangan (DSCR), rasio keuangan, makroekonomi, regresi data panel, perusahaan ritel